Silver ions cause oscillation of bacterial length of Escherichia coli - Venkata Rao Krishnamurthi (Nature Portfolio, 2019)
Abstract Silver (Ag) in various forms have recently gained broad interest and been revisited due to their promising antimicrobial effects. Here we report our study on the morphological dynamics of live bacteria when subjected to Ag+ ions. Using time-lapse microscopy, we observed oscillations of cell-length for a large fraction of bacteria exposed to 60 μM of Ag+ ions. In addition, we found that the responses of bacteria to Ag+ ions were heterogeneous. We quantified the oscillations of cell-length with power spectral density, which appeared different from that of bacteria growing in the absence of Ag+ ions. Furthermore, a model similar to the predator-prey argument was developed to understand the observed oscillations of cell-length upon exposure to Ag+ ions. This model not only successfully produced the oscillations but also explained the observed heterogeneity in the bacterial responses to Ag+ ions.